Preparation of Ibuprofen-Loaded Inhalable γCD-MOFs by Freeze-Drying Using the QbD Approach - Anett Motzwickler-Németh; Petra Party; Péter Simon; Milena Sorrenti; Rita Ambrus; Ildikó Csóka (MDPI AG, 2024)
Background/Objectives: Research on cyclodextrin-based metal-organic frameworks (CD-MOFs) is still in its infancy, but their potential for use in drug delivery-expressly in the lung-seems promising. We aimed to use the freeze-drying method to create a novel approach for preparing CD-MOFs. MOFs consisting of γ-cyclodextrin (γCD) and potassium cations (K+) were employed to encapsulate the poorly water-soluble model drug Ibuprofen (IBU) for the treatment of cystic fibrosis (CF). Methods: Using the LeanQbD® software (v2022), we designed the experiments based on the Quality by Design (QbD) concept. According to QbD, we identified the three most critical factors, which were the molar ratio of the IBU to the γCD, incubation time, and the percentage of the organic solvent. light-, scanning electron microscope (SEM) and laser diffraction were utilized to observe the morphology and particle size of the samples. In addition, the products were characterized by Differential Scanning Calorimetry (DSC), X-ray Powder Diffraction (XRPD), Fourier Transform Infrared Spectroscopy (FT-IR) and nuclear magnetic resonance spectroscopy (NMR). Results: Based on characterizations, we concluded that a γCD-MOF/IBU complex was also formed using the freeze-drying method. Using formulations with optimal aerodynamic properties, we achieved 38.10 ± 5.06 and 47.18 ± 4.18 Fine Particle Fraction% (FPF%) based on the Andersen Cascade Impactor measurement. With these formulations, we achieved a fast dissolution profile and increased IBU solubility. Conclusions: This research successfully demonstrates the innovative use of freeze-drying to produce γCD-MOFs for inhalable IBU delivery. The method enabled to modify the particle size, which was crucial for successful pulmonary intake, emphasizing the need for further investigation of these formulations as effective delivery systems.